2013
DOI: 10.1021/es400483k
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Properties and Stability of Graphene Oxide Nanomaterials in the Aquatic Environment

Abstract: While graphene oxide (GO) has been found to be the most toxic graphene-based nanomaterial, its environmental fate is still unexplored. In this study, the aggregation kinetics and stability of GO were investigated using time-resolved dynamic light scattering over a wide range of aquatic chemistries (pH, salt types (NaCl, MgCl2, CaCl2), ionic strength) relevant to natural and engineered systems. Although pH did not have a notable influence on GO stability from pH 4 to 10, salt type and ionic strength had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
415
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 516 publications
(474 citation statements)
references
References 51 publications
55
415
1
3
Order By: Relevance
“…S6. It is shown that the increase of HA concentrations had a negligible effect on the EMPs of FGO, consistent with the result of Chowdhury et al [36]. Addition of HA, however, enhanced the stabilization of FGO in water (Fig.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…S6. It is shown that the increase of HA concentrations had a negligible effect on the EMPs of FGO, consistent with the result of Chowdhury et al [36]. Addition of HA, however, enhanced the stabilization of FGO in water (Fig.…”
supporting
confidence: 91%
“…S8). Because HA did not affect the EMPs of FGO, steric repulsion imparted by the adsorbed HA macromolecules may be the dominant mechanism in FGO stabilization [36,37].…”
mentioning
confidence: 95%
“…The resulting GONPs had a planar structure with an average perimeter of 781 -502 nm, an average height of 0.9 -0.2 nm, and an average square root of the surface area of 179 -112 nm (Chowdhury et al, 2013;Duch et al, 2011). The modified Hummer's method was used to synthesize the GONPs used in this study and were reported to contain oxygen-bearing functional groups including carboxylic, carbonyl, and hydroxyl (Duch et al, 2011).…”
Section: Solution Chemistrymentioning
confidence: 99%
“…The GONP suspensions were created at an unadjusted pH since previous studies (Chowdhury et al, 2013;Lanphere et al, 2013) have shown that there is no significant effect on stability from pH 5 to 9. The artificial groundwater (Bolster et al, 1999) and surface water (Yip et al, 2011) suspensions were developed using recipes found in the literature and had an ionic strength (IS) of 3.78 and 1.74 mM, respectively.…”
Section: Solution Chemistrymentioning
confidence: 99%
See 1 more Smart Citation